Acute stroke therapy: A review - Peisker, Tomas; Koznar, Boris; Stetkarova, Ivana; Widimsky, Petr (Trends in cardiovascular medicine, 2017)
This review summarizes the modern early diagnosis and acute phase treatment of acute stroke. The guidelines for treatment of acute ischemic stroke underwent major changes in 2015 and endovascular therapy (catheter-based mechanical thrombectomy with a stent retriever) became the class IA indication for patients presenting within less than 6h from symptom onset who have proven occlusion of large intracerebral artery in anterior circulation. Acute stroke care organization should enable to perform effective revascularization therapy as soon as possible after the initial brain imaging whenever this examination provides indication for the procedure.
Keywords: Endovascular Procedures; Cerebrovascular Circulation; Thrombolytic Therapy; endovaskulární výkony; výsledek terapie; mozkový krevní oběh; Computed Tomography Angiography; cévní mozková příhoda; Predictive Value of Tests; trombektomie; prediktivní hodnota testů; časové faktory; trombolytická terapie; Time Factors; Acute stroke; lidé; Stroke; Mechanical thrombectomy; Treatment Outcome; Intravenous thrombolysis; Humans; Risk Factors; Stents; Thrombectomy; Cerebral Revascularization; rizikové faktory; Cerebral Angiography; CT angiografie; Stent retriever; stenty; mozková angiografie; revaskularizace mozku